ANALISIS TERBANG MELUNCUR (GLIDE FLIGHT) PESAWAT TERBANG STTA-12MXA - bahrun bahrun; Bangga Dirgantara Adiputra (Institut Teknologi Dirgantara Adisutjipto, 2020)
In designing the STTA-12MXA aircraft, analysis of the ability of the glide is one of the important aspects. The analysis was carried out using a numerical approach. There are 2 scenarios used to see the ability of the glide, namely the maximum distance and maximum flight time. The results showed that the maximum distance that the STTA-12MXA aircraft could reach when glide from 13500 ft is 64 km and for the maximum flight time is 23 minutes.